TPACK profile of biology teachers in the industrial revolution 4.0 era - Yenny Anwar; Sapira Permata Dewi; Selvi Riyanti (University of Muhammadiyah Malang, 2024)
Technological Pedagogical and Content Knowledge (TPACK) is very important in the process of developing professional teacher competencies in the era of the Industrial Revolution 4.0. The purpose of this study was to determine the profile of biology teachers TPACK on the classification of living things. This research is a descriptive study using a qualitative approach. Data collection techniques were carried out using questionnaires, CoRe&TPaP-eRs, and interviews. The sample was compiled using a saturated sampling technique with a total of ten respondents. The results indicated that biology teachers' TPACK skills must be improved. The results of the questionnaire consisting of 7 TPACK components, reaching 70.11% were categorized as good. The TK, PK, CK, and PCK components are in the excellent category, while the TCK, TPK, and TPACK components are still in the good category. The results of the CoRe & TPaP-eRs instrument covering 5 aspects show that the average of teacher’s TPACK reached 41%, in the Growing-TPACK category. The TPACK of biology teachers based on teaching experience is not so different. The results show that the length of teaching experience is not directly proportional to the growth of TPACK skills.